2023
DOI: 10.3390/insects14080674
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Antioxidant Peptides Derived from Cricket (Gryllus bimaculatus) Protein Fractions

Olumide Oluwatoyosi Fashakin,
Pipat Tangjaidee,
Kridsada Unban
et al.

Abstract: Crickets contain high protein content that can be used to improve nutrition but are less exploited. This study was conducted to isolate different Cricket Protein Fractions including albumin, globulin, glutelin, and prolamin. All fractions were characterized and hydrolyzed by commercial enzymes. The results showed that the glutelin fractions had the highest extraction yields with 53.9 ± 2.12% (p < 0.05). Moreover, glutelin hydrolysate fraction prepared by Alcalase with a 16.35 ±0.29% hydrolysis degree was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Similarly, a consistent trend in antioxidant activity was observed. Fashakin’s study showed that the smallest MW fraction (<3 kDa) of cricket protein hydrolyzed with Alcalase ® demonstrated the highest anti-radical ABTS activity with the values of 0.45 µmol Trolox eq./g, surpassing the activity of fractions with MW of (3 to 10) kDa and >10 kDa [ 89 ]. This consistency with prior research highlighted the trend that lower MW peptides often possess higher bioactivity, likely due to the presence of smaller peptide sequences facilitating binding to target proteins or free radicals [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a consistent trend in antioxidant activity was observed. Fashakin’s study showed that the smallest MW fraction (<3 kDa) of cricket protein hydrolyzed with Alcalase ® demonstrated the highest anti-radical ABTS activity with the values of 0.45 µmol Trolox eq./g, surpassing the activity of fractions with MW of (3 to 10) kDa and >10 kDa [ 89 ]. This consistency with prior research highlighted the trend that lower MW peptides often possess higher bioactivity, likely due to the presence of smaller peptide sequences facilitating binding to target proteins or free radicals [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have revealed the amino acid sequence with antioxidant capabilities in the PH derived from crickets. Fashakin et al (2023) revealed that ten identified peptides in PH from black cricket ( Gryllus bimaculatus ) were TEAPLNPK, EVGA, KLL, TGNLPGAAHPLLL, AHLLT, LSPLYE, AGVL, VAAV, VAGL, and QLL [ 89 ]. The amino acid composition showed a predominance of hydrophobic amino acids ((50 to 100)%), contributing to the peptides’ significant antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…33 The peptides YKPRP, PHGAP, and VGPPQ were able to interact with the residues of the enzyme active site for hypertension control via ACE inhibition. 34,35 In addition, the histidine, arginine, and lysine amino acid sequences present in these insects act as free radical scavengers to reduce oxidative damage and improve chronic diseases associated with obesity. 35,36 Consequently, the edible GA cricket has novel possibilities as a substitute protein and bioactive peptide dietary source.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, insect proteins are more digestible (79–98%) than plant-based proteins but are only slightly less digestible than animal-based proteins such as beef and egg white (100%) [ 92 ]. In addition, cricket ( Gryllus bimaculatus ) protein meets the requirements for human adults, and its amino acid sequence shows a prevalence of hydrophobic amino acids (50–100%) such as valine and leucine in the peptide chains, accounting for its high antioxidant activity [ 93 ]. Furthermore, the black soldier fly ( Hermetia illucens ) is one of the edible insect species chosen as the most promising for the commercial production of proteins, with numerous beneficial advantages to humans and the environment.…”
Section: Future Food Proteins—can They Fulfil Nutritional Needs?mentioning
confidence: 99%